TRANSPARENCY IN GOVERNMENT PROCUREMENT OF GOODS AND SERVICES: CHALLENGES AND SOLUTIONS - Hernita Hernita; Gunawan Widjaja (Adisam Publisher, 2025)
Government procurement of goods and services is a vital aspect of good governance. Transparency in the procurement process is key to preventing corruption, collusion, and nepotism, as well as improving accountability in the use of state budgets. However, the implementation of transparency still faces various challenges, such as limited access to information, complex regulations, low human resource capacity, political intervention, and weak supervision and law enforcement. This study uses a literature review method to identify the main challenges in transparency in government procurement of goods and services and to formulate effective solutions. The results of the review indicate that the implementation of an e-procurement system, strengthening regulations, improving human resource competencies, community involvement, and independent supervision are strategic steps that can increase transparency. With integrated solutions and commitment from all stakeholders, transparency in government procurement can be achieved sustainably, thereby supporting clean, efficient, and equitable development.